Botany class on trip though Poly Canyon in 1911 (1911)
Text on accompanying sheet reads: 'Mr. Pearson, teacher. Standing from left. Maude Cheda (Irwin) Mr. Pearson, Helen Sandercock Dorothy Edmonds, Tekla Johnson; Sitting. Eva Tenguary. She was a niece of Mark Train (Samuel Clemons) Lilabel Wade, daughter of a local doctor; Hazel Prince ?(not sure)'